2018
DOI: 10.1111/ijsw.12362
|View full text |Cite
|
Sign up to set email alerts
|

The perceived legitimacy of a basic income among Finnish food aid recipients

Abstract: Discussions on the pros and cons of a basic income (BI) have remained mainly at the ‘systemic level’. Based on survey and interview data, this study provides a ‘bottom‐up’ perspective on the legitimacy of the idea of a basic income among people queuing in breadlines in Helsinki in late 2016, who are assumed to be affected positively by this benefit. While general support for the idea is high, not everyone supports an unconditional BI. Despite the likely ‘objective interest’, a BI does not seem to be supported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…This suggests that (perceived) personal need and insecurity, as well as a preference for social equality affects BI opinions, aligning with the results from welfare attitude studies generally (Meier Jaeger, 2006;Roosma et al, 2014). However, Linnanvirta et al (2017) find that among their sample of poor Fins, the level of support for a BI, as well as the motives for and against it, do not differ substantively from the Finnish general population. Also, from a theoretical perspective, it is not immediately clear what kind of interest indicators and ideological positions would play which role.…”
Section: Possible Individual Characteristics Influencing Bi Supportsupporting
confidence: 71%
See 1 more Smart Citation
“…This suggests that (perceived) personal need and insecurity, as well as a preference for social equality affects BI opinions, aligning with the results from welfare attitude studies generally (Meier Jaeger, 2006;Roosma et al, 2014). However, Linnanvirta et al (2017) find that among their sample of poor Fins, the level of support for a BI, as well as the motives for and against it, do not differ substantively from the Finnish general population. Also, from a theoretical perspective, it is not immediately clear what kind of interest indicators and ideological positions would play which role.…”
Section: Possible Individual Characteristics Influencing Bi Supportsupporting
confidence: 71%
“…However, under more detailed specifications, a BI might drop substantively in popularity. Especially, the suggestion that not only natives, but also immigrants would be covered by a BI lowered support levels (Bay and Pedersen, 2006; Linnanvirta et al, 2017; Stadelmann-Steffen and Dermont, 2017), and reference to the possible (cost) consequences of a BI, like increased taxes or reduced (other) benefits, had an eroding effect in the United Kingdom (Ipsos, 2017).…”
Section: Public Opinion On Bimentioning
confidence: 99%
“…The focus of the study is on the proportion of households using basic social assistance as a last resort which is means‐tested (cf. Ilmakunnas, 2018; Ilmakunnas & Moisio, 2019; Kuivalainen, 2005; Linnanvirta et al, 2019). Basic social assistance is arranged by the State through the National Insurance Agency.…”
Section: Methodsmentioning
confidence: 99%
“…Abundant research has found that people with a lower income and educational attainment, and those in a higher risk position in the labor market (e.g., temporary workers or the unemployed) show more positive attitudes toward UBI (Bay & Pedersen, 2006; Lim & Tanaka, 2019; Roosma & van Oorschot, 2020; Shin et al., 2021; Stadelmann‐Steffen & Dermont, 2020; Vlandas, 2021). Similarly, perceived income uncertainty (Lee, 2018) and the perception that a UBI would improve one's current economic situation (Linnanvirta et al., 2019) are related to greater UBI support. Importantly, these findings corroborate previous literature that states the importance of considering both objective and subjective indicators of self‐interest when studying welfare attitudes (e.g., Brown‐Iannuzzi et al., 2015; Kevins et al., 2019).…”
Section: Unconditional Basic Income In Spain: An Overview Of the Poli...mentioning
confidence: 99%